Association of vitamin D deficiency and disease activity in systemic lupus erythematosus patients: Two-year follow-up study - Ainan ARSHAD; Saad Bin Zafar MAHMOOD; Ahmed AYAZ; Adil Al Karim MANJI; Akash Kumar AHUJA (Archives of Rheumatology, 2021)
Objectives: This study aims to determine the prevalence of vitamin D deficiency in Pakistani systemic lupus erythematosus (SLE) patients and the effect of vitamin D deficiency on the severity and outcomes of SLE. Patients and methods: This retrospective study evaluated SLE patients presenting to our hospital between January 2009 and December 2018. A total of 98 patients (13 males, 85 females; mean age 39.8±14.9 years; range, 16 to 73 years) with vitamin D levels available at the time of diagnosis were included in the study. Disease activity was measured using SLE disease activity score at the time of diagnosis and at the two-year mark. Results: Sixty-five patients were deficient in Vitamin D and out of those 46 were severely deficient. The severe disease group had more patients with vitamin D deficiency at both visits (43/78 and 33/46) while patients in remission all had normal vitamin D (12/12 and 14/14) (p≤0.001). Conclusion: Vitamin D deficiency is common in SLE patients and also significantly associated with increased disease activity at the time of diagnosis and at the two-year mark. We hope this study becomes a platform for the global medical community to come together and implement early screen- ing and monitoring of vitamin D levels and to determine the optimal level of supplementation for prevention of poor outcomes in SLE.